Estimasi Ketinggian Planetary Boundary Layer Berdasarkan Data Radiosonde RS92 Menggunakan Gradien Vertikal Kelembapan Udara - M. Rido Fadilah; Syahril Rizal R I (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This study observes the vertical profile of the troposphere using data from radiosondes that are periodically applied to the upper air. The instrument used in this observation consists of sensors that measure weather parameters such as temperature, pressure, air humidity, wind direction and speed. Every 00:00 UTC and 12:00 UTC, the instrument is flown to transmit data on altitude, temperature, wind density and direction, humidity and air pressure from the atmosphere to the earth's surface. The data collected will be used to understand convective processes in the atmosphere and their relation to life on earth. These observations play an important role in predicting and understanding weather and climate phenomena, and provide useful information for various sectors such as transportation, agriculture and public health. However, radiosonde observations are costly and complicated, so not all meteorological stations can make observations using this method. In addition, radiosonde observations also have limitations on the level of data density produced. Therefore, it is necessary to develop a radiosonde system that is easy to implement and low cost. This system can help increase the data density of upper-air observations and provide more accurate weather information. Radiosonde estimation can also help overcome limitations in radiosonde observations and improve the efficiency of weather observations. Research methods that use radiosondes are also known as radiosonde flight research. This research method falls into the category of "Observational Research" or "Observational Experimental Research". The results of the research conducted on 6x balloon flight experiments using radiosonde resulted in extreme points at different altitudes and relative humidity (RH). The first extreme point at altitude: 18735 and RH: 4.24. The second extreme point at altitude: 1144 and RH: 97.56. The third extreme point at altitude: 30 and RH: 97.63. The fourth extreme point at altitude: 35 and RH: 94.12. The fifth extreme point at altitude: 38 and RH: 97.63. And the sixth extreme point at altitude: 1073 and RH: 86.19.